Advanced analytical models : over 800 models and 300 applications from the Basel II Accord to Wall Street and beyond - Mun, Johnathan (Wiley, 2008)
More practitioners are turning to financial modeling to quantitatively estimate the value of a security. This text offers a set of 250 models that cover a wide range of industries and applications, including banking, manufacturing, military, pharmaceutical, financial services, oil and gas, operations research, and more.